EFFECTS OF MECHANICAL VIBRATION ON THE HEAT TRANSFER CHARACTERISTICS OF TUBULAR TURBULENT FLOW - MOHAMMED, AZEZ MAJEED MOHAMMED (Fırat Üniveristesi, 2018)
Bu tezde turbulatorlü bir türbülanslı akıma titreşimin etkisi deneysel olarak incelenmiştir. İç içe geçmiş ısı değiştirgecinde iç akışa sinüs, çörp ve rastgele gürültü sinyalleri gibi farklı titreşim türlerinin etkisini bulmak üzere deneyler yapılmıştır. Deneylerde akışkan olarak Reynolds sayısının 10,000 ila 50,000 değerleri arasındaki hava kullanılmıştır. Mekanik titreşim jeneratörünün frekansı ve titreşim genliği deneylerdeki diğer önemli değişken parametrelerdir. Bu çalışmada Isı transferi laboratuvarında daha önceden kurulmuş olan bir deney düzeneği kullanılmıştır. İç içe borulu ısı değiştiricisi içerisinde kullanılan türbülatörler üzerinde kıvrımlı şeritler bulunan uzun çubuklar şeklindedir. Deney düzeneğinde içteki borunun dışından sıcak su buharı geçirilmiştir. Bu buhar iç borunun dış yüzeyiyle sürekli temas halinde olduğundan böylece sabit sıcaklık sınır şartı sağlanmıştır. Isı transferini ve basınç farkını elde etmek üzere sıcaklık ve basınç ölçümleri yapılmıştır. İç borunun içerisinden hava radyal fan ile gönderilmiştir. Farklı hava hızları elde etmek için fan bir invertör yardımıyla ayarlanmıştır. Titreşimin etkisini görmek üzere bir mekanik titreşim test düzeneği kullanılmıştır. frekans ve ivme (genlik) geniş bir aralıkta değiştirilmiştir. Sinüs, çörp ve rastgele gürültü sinyal türleri uygulanarak titreşimin ısı transferi yani Nusselt sayısı üzerindeki etkisi araştırılmıştır. Titreşimsiz durum için sonuçlar elde edilerek her iki sonuç kıyaslanmıştır. Ve neticede ısı transferinin ve basınç kaybının titreşimle beraber arttığı görülmüştür. Sonuç olarak görülmüştür ki, frekans, genlik ve sinyal tipi değişimleri ne olursa olsun titreşim uygulamak ısı transferini ve basınç kaybını aynı anda yüksek yüzde oranlarında arttırmıştır. Örneğin, ısı transferi test edilen üç türbülatör tipi için Tip 1'de 116%, Tip 2'de 105% ve Tip 3'de 64% şeklinde artmıştır. Sürtünme faktörü için bu artışlar Tip 1'de 35%, Tip 2'de 61% ve Tip 3'de 95% şeklinde olmuştur.

In this thesis, the effects of vibration on tabulated turbulent flow are experimentally analyzed. The experiments are performed to investigate the effects of sinusoidal, chirp and random noise vibrations on heat transfer characteristics of internal flow in a concentric type direct flow heat exchanger. Air is used as the working fluid with inlet Reynolds numbers varying between 10,000 and 50,000. The various values of frequencies of the mechanical vibration generator and vibration accelerations are the other important parameters in the experiments. An experimental setup which was already set in Heat Transfer Laboratory is used in this work. The turbulators used in the concentric heat exchanger are somehow corrugated tapes. In the experimental assembly, hot water vapor is send to the annulus between the inner pipe and the outer pipe. This saturated water vapor is in contact with the outer surface of the inner pipe at all times. Thus, the constant temperature boundary condition is met on the outer surface of the inner pipe. The temperature and pressure measurements are performed to obtain heat transfer and pressure drop variations. Air is passed through the inner pipe throughout the experiment using a radial fan. The fan setting is changed with the help of an inverter to obtain different flow velocities. The influence of the vibration is tested by using a mechanical vibration test unit. The frequency and accelerations (amplitude) are changed in a wide range area. The sine, chirp and random-noise signal types are imposed on the heat exchanger. Hence effects of the vibration on heat transfer are shown by means of Nusselt number. The simultaneously increment of pressure loss is also measured. Furthermore, the effects of vibration on the smooth tube internal turbulent flow and heat transfer are analyzed for comparison. As a results it was observed that, regardless of the variation of the frequency, amplitude or signal type, applying vibration to the turbulator increases the heat transfer and pressure loss simultaneously, with high percentages. For example, the heat transfer increases with the percentages of 116%, 105% and 64%, respectively for Type 1, Type 2 and Type 3. The enhancement percentages of the friction factor is about 35%, 61% and 95% respectively for Type 1, Type 2 and Type 3.
Borulu türbülanslı akışta mekanik titreşimin ısı transferi karakteristiğine etkisi
Keywords: Makine Mühendisliği